AN ANALYSIS OF CULTURAL ADJUSTMENT BASED ON "THE LAST SAMURAI" MOVIE - Nia Kurniawati, - (2010)
A person who is going abroad or living in a new society/culture for a long time will experience cultural adjustment process. The process of adjustment means getting accustomed with everything in the new culture. To get a better point of view of how a newcomer experience stages of cultural adjustment process and how he/she solve the problems and difficulties that faced in experiencing the adjustment, this research analyzed the main character Algren experienced cultural adjustment process in "The Last Samurai" movie. This research applied qualitative method with the script of the movie as the subject of the study. The data gained from the script that then analyzed in order to categorize the script based on each stage of the W pattern of cultural adjustment process. Based on analysis of the script of the movie, Algren as the main character only experienced three stages of cultural adjustment: culture shock, initial adjustment, and acceptance & integration. Honeymoon period and mental isolation is not experienced by Algren. It is expected that the research will give valuable and meaningful inputs for readers who want to enter new society/culture. Especially, this research expected give benefits for English students who are learning Intercultural Communication, to enrich the material about cultural adjustment process.